Drosophila Mtm and class II PI3K coregulate a PI(3)P pool with cortical and endolysosomal functions. - Velichkova, M.; Juan, J.; Kadandale, P.; Jean, S.; Ribeiro, I.; Raman, V.; Stefan, C.; Kiger, A.A. (Journal of Cell Biology, 2010)
Reversible phosphoinositide phosphorylation provides a dynamic membrane code that balances opposing cell functions. However, in vivo regulatory relationships between specific kinases, phosphatases, and phosphoinositide subpools are not clear. We identified myotubularin (mtm), a Drosophila melanogaster MTM1/MTMR2 phosphoinositide phosphatase, as necessary and sufficient for immune cell protrusion formation and recruitment to wounds. Mtm-mediated turnover of endosomal phosphatidylinositol 3-phosphate (PI(3)P) pools generated by both class II and III phosphatidylinositol 3-kinases (Pi3K68D and Vps34, respectively) is needed to down-regulate membrane influx, promote efflux, and maintain endolysosomal homeostasis. Endocytosis, but not endolysosomal size, contributes to cortical remodeling by mtm function. We propose that Mtm-dependent regulation of an endosomal PI(3)P pool has separable consequences for endolysosomal homeostasis and cortical remodeling. Pi3K68D depletion (but not Vps34) rescues protrusion and distribution defects in mtm-deficient immune cells and restores functions in other tissues essential for viability. The broad interactions between mtm and class II Pi3K68D suggest a novel strategy for rebalancing PI(3)P-mediated cell functions in MTM-related human disease.